Public Service Performance at the Transportation Office of Buol Regency, Indonesia: A Qualitative Assessmen - Febryany Febryany; Yanti Aneta; Romy Tantu (Public Policy Journal, 2026)
This study examines the performance of public services at the Transportation Office of Buol Regency, Indonesia. The research was motivated by persistent service delivery challenges, particularly the unavailability of adequate motor vehicle testing facilities and the absence of an integrated digital service platform. A descriptive qualitative approach was employed, utilizing interviews, observation, and document analysis as the primary data collection techniques. Data were analyzed through data reduction, data display, and conclusion drawing and verification. The findings indicate that public service performance has not yet achieved optimal standards. Major constraints include inadequate facilities and infrastructure, limited human resource capacity, and the lack of a digital-based information and service system. These limitations have reduced service productivity, weakened service quality, restricted responsiveness, and hindered accountability. As a consequence, residents are required to access certain transportation services, particularly vehicle testing, outside the regency. The study concludes that strengthening infrastructure, enhancing staff competencies, and implementing digital public service innovations are essential to improving service effectiveness and achieving higher standards of public sector performance.